Tourism and its impacts projected to grow substantially in Antarctica - Rodolfo De Oliveira Anderson; Jasmine Lee; Kees Bastmeijer; Steven Chown (2024)
Abstract Antarctica, a region devoted to peace and science, faces an uncertain future amid expanding tourism, which is thought to cause cumulative environmental impacts. Much focus now exists on developing a regulatory framework for Antarctic tourism, but discussions on such a framework lack quantitative projections of tourism growth and its impacts. Here, based on historical data on visitor landings, we use the shared socioeconomic pathways to project numbers of future landings and their impacts. We show that under most scenarios the numbers of landings could grow dramatically by the end of the century, with the high-emission scenarios leading to a 5-fold increase of tourist activities in Antarctica. Landing numbers could be as high as 2 million landings by 2100. Industry-led norms or country-by-country regulation is likely to be less effective for mitigating impacts than an Antarctic Treaty System agreed regulatory framework that is binding. Contents Scripts used to assess the impacts of tourism on Antarctica and forecast tourist landings up to 2100. R scripts: MASTER - oneimpact.R : code for evaluation of the tourism impacts on penguin colonies, vegetation, and Antarctic Specially Protected Areas. MASTER - Forecasting Tourism.R : code for forecasting the number of tourist landings on Antartica based on Shared Socioeconomic parthways scenarios. Data Tourism data landings : Visitors landing data, from the 1989/90 season to the 2022/23 season were downloaded from the IAATO data repository in September 2023 (https://iaato.org/information-resources/data-statistics/). Economic indicators : Global gross domestic product (GDP) and GDP growth (% per year) were extractec from the World Bank Database for the years from 1989 to 2022 ( https://data.worldbank.org/ ). Spatial data on biodiversity values: Coordinates and/or shapefiles for penguin colonies, vegetation, and Antarctic Specially Protected Areas (ASPAs) were extracted from Mapping Application for Penguin Population and Projected Dynamics (MAPPPD; Humphries et ...